2019
DOI: 10.1177/0958305x19854542
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between energy consumption and gross domestic product in Hong Kong (1992–2015): Evidence from sectoral analysis and implications on future energy policy

Abstract: The causal relationship between energy consumption and gross domestic product in Hong Kong from 1992 to 2015 is investigated in this study. Different from the previous studies focusing on the causal relationship between total energy consumption and total gross domestic product per capita, this study further investigates the causal relationship from sectoral perspective, including residential, commercial, industrial and transportation sectors. For each sector, the time series data of sectoral energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In general, since the era of industrialization, every country has competed to produce and increase domestic productivity (Almer & Winkler, 2017;Atik, 2012;Ghosh, 2019;Korkut et al, 2017). However, not many countries are aware of the impact (Dadhich et al, 2021;Li & Jiang, 2018;Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In general, since the era of industrialization, every country has competed to produce and increase domestic productivity (Almer & Winkler, 2017;Atik, 2012;Ghosh, 2019;Korkut et al, 2017). However, not many countries are aware of the impact (Dadhich et al, 2021;Li & Jiang, 2018;Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Wu 16 confirmed asymmetric effect of non-clean energy on economic growth. Zhang et al 17 use sectoral based analysis to explore the link between energy consumption and output. For industrial sector, the findings confirmed the unidirectional relationship between energy consumption to output.…”
Section: Introductionmentioning
confidence: 99%